ANSWERING ASSUMPTIONS REGARDING THE INCONSISTENCY OF 'AWDUDH-DHOMIR IN THE QUR'AN - Sajidan Insi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The accusations attached to the Qur'an has happened even since the time of the Prophet Muhammad SAW, and Allah challenged for anyone to make​ letter such as those in the Koran. In this day and age of accusations against the Qur'an is done through orientalism . The colonizers attack Islam in a way confidential through orientalist . One of the the target is eradicate Arabic and revoke it from people Islam . One of the branch indicated science​ existence accusations by orientalists is knowledge syntax ( nahw ), more especially in the chapter ' awdudh- dhomīr claimed happen inaccuracy in return dhomīr his to the previous word . This is become reason they For weaken the Qur'an in the heart people Muslims and also for accuse that the Qur'an is a holy book that is not ma'shūm( awake) from error ). Because of that that , in this article will analyze as well as answer assumptions about mismatch ' awdudh-dhomīr in the Qur'an.